The Influence of Attractiveness, E-Wom, and Social Factors on Interest in Visiting Tugu Khatulistiwa, Pontianak City - Arweni, Arweni; Octaviani, Dina; Ariffin, Muchammad; Rawa, Ricola Dewi; Kelvin , Kelvin (P3KM Politeknik Pertanian Negeri Samarinda, 2024)
This study discusses the influence of attractiveness, Electronic Word of Mouth (E-WOM) and social factors on the interest in visiting Tugu Khatulistiwa of Pontianak City in the tourism sector. This research is focused on the people of Pontianak City who have an interest in visiting Tugu Khatulistiwa. In this research, the type and data to be used is quantitative research with a survey method approach to achieve research objectives, namely identifying the role of e-wom appeal and social factors on visiting interest at the Tugu Khatulistiwa, Pontianak City. Using purposive sampling method involving 150 respondents. Hypothesis testing of this study was carried out with Structural Equation Modeling (SEM-PLS) with the Warp-PLS version 8.0 analysis tool. The results of this study reveal the important role of Attractiveness, E-WOM and Social Factors in influencing tourist interest in visiting a tourist destination. From the calculation of the coefficient value and significance value, there is a positive influence between Attractiveness and E-Wom on the interest in visiting the Pontianak Tugu Khatulistiwa, while the coefficient value and significance value of Social Factors do not have a positive influence on the interest in visiting the Pontianak Tugu Khatulistiwa. These findings provide valuable insights for the tourism industry in developing more effective and attractive marketing strategies. The practical implications of this research can help related parties in increasing attractiveness, promotion and factors that can shape a person's interest in visiting Tugu Khatulistiwa